2007
DOI: 10.1103/physrevc.76.014307
|View full text |Cite
|
Sign up to set email alerts
|

Low-spin collective behavior in the transitional nucleiMo86,88

Abstract: Low-spin structures in 86,88 Mo were populated using the 58 Ni( 36 Ar, xαyp) heavy-ion fusion-evaporation reaction at a beam energy of 111 MeV. Charged particles and γ rays were emitted in the reactions and detected by the DIAMANT CsI ball and the EXOGAM Ge array, respectively. In addition to the previously reported low-to-medium spin states in these nuclei, new low-spin structures were observed. Angular correlation and linear polarization measurements were performed in order to unambiguously determine the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…6 we plotted the experimental spectra of three even-A neutron-deficient Pd isotopes. As one would expect, in 96 Pd with four proton holes with respect to 100 Sn, the positions of the energy levels correspond to a (g 9/2 ) 2 λ isovector pairing (or seniority) spectrum. In particular, the yrast 8 + state, which has the largest spin among the v = 2 states, shows a typical pattern for isomeric states as induced by the seniority coupling.…”
Section: Seniority and Np Coupling Schemesmentioning
confidence: 99%
See 4 more Smart Citations
“…6 we plotted the experimental spectra of three even-A neutron-deficient Pd isotopes. As one would expect, in 96 Pd with four proton holes with respect to 100 Sn, the positions of the energy levels correspond to a (g 9/2 ) 2 λ isovector pairing (or seniority) spectrum. In particular, the yrast 8 + state, which has the largest spin among the v = 2 states, shows a typical pattern for isomeric states as induced by the seniority coupling.…”
Section: Seniority and Np Coupling Schemesmentioning
confidence: 99%
“…This is the heaviest N = Z nucleus with measured spectrum so far. It was suggested that in this nucleus, as well as in neighboring nuclei like 96 Cd, the properties of the low-lying states can be classified by a spin-aligned np pair coupling scheme [62,63]. That is, the ground state wave functions do not consist mainly of pairs of neutrons (νν) and protons (ππ) coupled to zero angular momenta, but rather of isoscalar np pairs (νπ) coupled to the maximum angular momentum J, which in the shell 0g 9/2 is J = 9 [62,63].…”
Section: Seniority and Np Coupling Schemesmentioning
confidence: 99%
See 3 more Smart Citations